2018
DOI: 10.1111/ecc.12877
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cancer families’ participation in whole-genome sequencing research in Denmark: Parent perspectives

Abstract: With an impending introduction of genome sequencing into paediatric oncology to facilitate personalised medicine, this study examines parent perspectives on participating in whole genome sequencing (WGS) research in the difficult weeks following diagnosis. As an embedded part of Sequencing Tumor and Germline DNA-Implications and National Guidelines (STAGING), a project aiming to implement WGS of all newly diagnosed paediatric cancer patients in Denmark, a parent perspective study was conducted by a clinical ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…This is doable with counselling provided by doctors or genetic counselors who have specialized within this field. We have recently shown that parents overall are keen to participate in genetic research of children with cancer [27], and that most agree to have findings in cancer genes reported back to them.…”
Section: Discussionmentioning
confidence: 84%
“…This is doable with counselling provided by doctors or genetic counselors who have specialized within this field. We have recently shown that parents overall are keen to participate in genetic research of children with cancer [27], and that most agree to have findings in cancer genes reported back to them.…”
Section: Discussionmentioning
confidence: 84%
“…High levels of interest in learning about results were also expressed by participants making actual decisions about whether they wanted to receive results [ 1 , 2 , 12 ]. Several studies observed that return of results was a key reason for research participation [ 2 , 4 , 69 , 70 ] and a survey exploring participation across several Clinical Sequencing Exploratory Research (CSER) consortium sites showed that only 5% who declined did so because they did not want research results returned [ 71 ].…”
Section: Views On Return Of Study-specific Resultsmentioning
confidence: 99%
“…Notably, remission was reached with current medulloblastoma treatment protocols despite the PTEN status. As certain countries are beginning to provide whole‐genome sequencing for all newly diagnosed pediatric cancer patients (Byrjalsen et al., 2018), coincidental germline variants may confound the search for true genetic predisposition in pediatric cancer. We therefore suggest that the genetic testing of young patients with medulloblastoma should include the PTEN gene in addition to the APC , BRCA2 , PALB2 , PTCH1 , SUFU and TP53 genes with well‐defined associations to medulloblastoma to characterize the role of PTEN in the development of medulloblastoma.…”
Section: Discussionmentioning
confidence: 99%